Taxonomic status of Pseudopaludicola riopiedadensis Mercadal de Barrio and Barrio, 1994 (Anura, Leptodactylidae, Leiuperinae) - Cardozo, Dario Elbio (2013)
Pseudopaludicola riopiedadensiswas described by Mercadal de Barrio and Barrio (1994) based on two adult females collected by Luiz Dino Vizotto in 1963 from Rio Piedade, São José do Rio Preto, São Paulo, Brazil. This taxon was differentiated from P. ternetzi based on a series of qualitative and morphometric characters. Nevertheless, the original description and the type material of P. ternetzi were not considered by Mercadal de Barrio and Barrio, and the morphological variation of P. ternetzi was not documented. This work reviews the sample collected by Vizotto in P. riopiedadensis type locality, evaluates the advertisement calls obtained from such population, the two vouchers assigned to P. riopiedadensis, and a large data set, including type specimens of P. ternetzito document the morphological variation along its known distribution. Results indicate that P. riopiedadensis was described on the basis of highly variable characters applied to a small sample and share the unique P. ternetzi autapomorphy, a robust body structure with immaculate belly. The lack of differentiation in both advertisement call and morphology rejects the status of P. riopiedadensis as distinct species, and we therefore suggest to formally consider P. riopiedadensis as junior synonym of P. ternetzi